MULTISENSORY APPROACH IN QURANIC READING WITH DYSLEXIA: A SCOPUS-BASED BIBLIOMETRIC ANALYSIS - Anuar, Nur Liyana Athirah; Muhamad, Norhisham; Mohd Nawi, Nur Syifaa; Salleh, Khadijah Aini (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
The studies on multisensory research in reading the Qur’an by dyslexic students have been increasing in number, demonstrating a growing academic interest in the inclusive and research-based approaches to the pedagogical process in the religious and special educational contexts. Regardless of this development, there is little systemic review of the trend of publications, influential articles, thematic focus, and global research cooperation in this area. To fill this gap, the current study is a thorough bibliometric analysis to trace the intellectual framework and the worldwide research context of the multisensory technique of Qur’an reading among students with dyslexia. A screening process was performed based on the advanced search query of the Scopus database to retrieve data on the topic, and a total of 298 relevant publications were obtained in the final dataset. Scopus Analyzer was also used to analyze the trend in publications, types of documents, citation patterns, and productivity at the country level. Cleaning and harmonization of data were carried out in OpenRefine so that there was consistency in author names, keywords, and affiliations. VOSviewer was used to produce network visualizations based on the co-occurrence of keywords and international cooperation to find out the most prevalent research topics and collaborative strategies. The findings show that the number of publications has significantly grown in recent years, which could indicate an increased academic interest in multisensory and inclusive pedagogy in regard to the Qur’an. Several articles with high citations are found as the classical ones, and the keyword analysis demonstrates that there are strong thematic relationships between the following: dyslexia, reading, learning disabilities, multisensory instruction, and inclusive education. The country analysis demonstrates that the output of research is localized in a few countries, and there are different levels of international cooperation. In general, Bibliometric analysis traces the evolution of the field, areas of research interest, and partnerships to inform future multisensory Qur’an reading for dyslexics.